Strafford's 'spirit' at the royalist court: Sir George Radcliffe and Irish affairs, 1643–5. Issue 164 (November 2019) - Pogson, Fiona
Abstract: This article examines how the handling of Irish affairs at the civil-war court was observed, commented upon, and probably influenced, by a man who had been at the heart of Irish government during the previous decade. It argues that the presence of Sir George Radcliffe, arguably Thomas Wentworth, earl of Strafford's closest advisor, at the royalist court in Oxford was significant in a number of respects. His surviving correspondence reveals the extent to which he was able to advise and support the newly-appointed lord lieutenant of Ireland, the marquis of Ormond. His letters also cast light on the politics of the civil-war court, in particular on how he, as an essentially second-level figure, worked flexibly with both secretaries of state. This article argues that Radcliffe's discussions with secretary of state, George Lord Digby, provided an important means by which Strafford's influence could make itself felt at the Oxford court, particularly during the 1644 negotiations with the Confederate commissioners. The pursuit of forceful, contentious policies by the former Irish administration and its contemptuous attitude towards critics, however, ensured that Radcliffe's presence at Oxford was probably unwelcome to many at court and failed to advance his career.